2010
DOI: 10.1091/mbc.e10-01-0047
|View full text |Cite
|
Sign up to set email alerts
|

LRPPRC and SLIRP Interact in a Ribonucleoprotein Complex That Regulates Posttranscriptional Gene Expression in Mitochondria

Abstract: The PPR family protein LRPPRC is implicated in the French Canadian variant of Leigh syndrome, a fatal neurodegenerative disease. LRPPRC functions in posttranscriptional mitochondrial gene expression as part of an RNP complex with SLIRP, a stem-loop RNA-binding protein, to regulate the stability and handling of mature mRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
292
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(320 citation statements)
references
References 25 publications
27
292
0
1
Order By: Relevance
“…LRPPRC (leucine-rich pentatricopeptide repeat containing) is a RBP that associates with both nuclear and mitochondrial mRNAs (Mili and Piñol-Roma 2003). Some evidence implicates LRPPRC in nuclear mRNA export, while mitochondrial LRPPRC controls RNA processing and translation (Sasarman et al 2010;Chujo et al 2012). Thus, LRPPRC could be involved in rRNP export from the nucleus, akin to what has been described for mRNA export.…”
Section: Identification Of Previously Unrecognized Ribosomal Rbpsmentioning
confidence: 99%
“…LRPPRC (leucine-rich pentatricopeptide repeat containing) is a RBP that associates with both nuclear and mitochondrial mRNAs (Mili and Piñol-Roma 2003). Some evidence implicates LRPPRC in nuclear mRNA export, while mitochondrial LRPPRC controls RNA processing and translation (Sasarman et al 2010;Chujo et al 2012). Thus, LRPPRC could be involved in rRNP export from the nucleus, akin to what has been described for mRNA export.…”
Section: Identification Of Previously Unrecognized Ribosomal Rbpsmentioning
confidence: 99%
“…44 The mammalian mitochondrial PPR protein, LRPPRC, which is important for polyadenylation and translation, forms an intimate complex with another RNA-binding protein, SLIRP, such that each protein requires the other for their stability. [69][70][71] Importantly, the editing PPR proteins of Arabidopsis must associate with multiple organelle RNA editing factor (MORF) family proteins or, in some cases, an autonomous DYW domain protein, DYW1, to deaminate their target RNA bases. [72][73][74][75] To date, a complete description of the proteins required for RNA editing has not been elucidated.…”
Section: Future Directions: Understanding and Engineering Ppr Proteinsmentioning
confidence: 99%
“…24 SLIRP is part of a ribonucleoprotein complex that regulates posttranscriptional gene expression in mitochondria. 29 In this contest, SLIRP interacts with LRPPRC and knockdown of either SLIRP 24 or LRPPRC 25 results in similar decreases in mitochondrial mRNA levels, indicating that the LRPPRC/SLIRP complex has a specific role in mRNA maturation or stabilization after transcription in mitochondria. In particular, it was demonstrated that the LRPPRC/SLIRP complex suppresses the mRNA degradation and promotes polyadenylation in human mitochondria.…”
Section: Discussionmentioning
confidence: 76%